Sociodemographic Factors Associated with Women’s Perspectives on Male Involvement in Antenatal Care, Labour, and Childbirth - Shamsudeen Mohammed; Ibrahim Yakubu; Issahaku Awal (Journal of Pregnancy)
Background. Evidence suggests that in patriarchal societies such as Ghana, access to and survival of maternal and child healthcare services require the active involvement of men. However, interventions to promote men’s involvement in maternal and child health care are less likely to succeed if the views and concerns of women are not considered. This study provides an understanding of women’s perspective on men’s involvement in antenatal care, labour, and childbirth in the Northern Region of Ghana. Methods. Data for this cross‐sectional study were collected from 300 pregnant women using a structured questionnaire. Logistic regression models were then used to determine the socio‐demographic factors associated with women’s perspectives on men’s involvement in antenatal care, labour, and childbirth. Results. The mean age of the participants was 28 (SD = 5.21) years. More than four-fifths of the women in this study express the desire for male partner involment in natenatal care (ANC) services (n = 258, 86%) and as companions during labour and child birth (n = 254, 84.7%). We found that married women were 9.8 times more likely (95%CI 1.59, 60.81) to encourage male involvement in ANC compared to women who were unmarried. The probability of encouraging male involvement in ANC decreased with increased level of education among the women while support for male companionship during childbirth increased significantly with an increased level of education. After accounting for the effect of other significant covariates, there was good evidence to suggest that married women (p = 0.002), women with only primary/Junior High School education (p = 0.048) and those with two (p = 0.010), three (p =  0.008), or ≥4 (p = 0.044) previous pregnancies had a desire for male partner involvement in ANC while women who attained secondary (p = 0.004) or tertiary (p = 0.001) level education expressed the desire for male companionship in labour and childbirth in the adjusted model. Conclusion. Male involvement in antenatal care, labour, and childbirth received overwhelming support from the women in this study.